THE EFFECT OF ALKALI METAL HALIDES ON THE STRUCTURE OF GLYCEROL FROM VISCOSITY B COEFFICIENT MEASUREMENTS (Sciences & Technology. A, exactes sciences, 2002)
Viscosity B‑coefficients in glycerol obtained at 25 °C for many salts by a rearrangement in the Jones‑Dole expression are compared with those calculated applying existing theories, based on the model of hard‑charged spheres moving in a solvent continuum. Specific agreement between theory and experiment was not generally good. While the results show that Einstein’s relation can be applied to large aqueous ions, provided that the true volume‑fraction of the ions in solution can be ascertained; this expression does not lead to accurate B‑values in glycerol. For the ion‑size dependence of the B‑coefficient in aqueous solutions, Clark’s theoretical predictions agree with experiments qualitatively, in the case of glycerol, however, the model shows limitations even for small ions, for which the dielectric friction theory is expected to be applicable. Finally, all the above theories give a positive B‑coefficient, while experimental evidences showed that B could be negative.